2013
DOI: 10.1111/jpc.12464
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of periorbital infantile haemangiomas: A systematic literature review on propranolol or steroids

Abstract: Propranolol may represent an effective therapy for periorbital IHs compared with the use of corticosteroids; however, further randomised control studies are needed to compare adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 67 publications
0
12
0
2
Order By: Relevance
“…Studies show that repeat injections of 20 mg of TA are required (one to four injections at monthly intervals) and the response rate is better in patients with recent onset of upper lid retraction or active disease. Xu et al noted an improvement in 83.3% of patients with symptom duration less than 6 months, compared to 36.4% who responded if symptoms were greater than 6 months. Joos et al showed that a superior orbital peri‐levator injection technique improved lid retraction and demonstrated reduction in size of the levator/superior rectus complex on MRI imaging after repeat injections.…”
Section: Uses Of Locally Administered Steroidsmentioning
confidence: 99%
“…Studies show that repeat injections of 20 mg of TA are required (one to four injections at monthly intervals) and the response rate is better in patients with recent onset of upper lid retraction or active disease. Xu et al noted an improvement in 83.3% of patients with symptom duration less than 6 months, compared to 36.4% who responded if symptoms were greater than 6 months. Joos et al showed that a superior orbital peri‐levator injection technique improved lid retraction and demonstrated reduction in size of the levator/superior rectus complex on MRI imaging after repeat injections.…”
Section: Uses Of Locally Administered Steroidsmentioning
confidence: 99%
“…In addition, in meta-analysis of 16 studies (2,629 cases) and 25 studies (795) published in 1965-2012, 69% of the patients responded to 12-month corticosteroid therapy, but the response rate to propranolol was 97% with a significant difference. 191 In periorbital hemangiomas, the response rate to propranolol was found to be significantly higher than that to corticosteroid by meta-analysis of papers published before 2013, 192 and propranolol showed the strongest effect against airway hemangiomas compared with steroid, CO 2 laser, and vincristine on meta-analysis. 193,194 From these observations, we concluded that propranolol was significantly more effective than placebo and to be similarly effective compared with corticosteroid.…”
Section: Cq14: Is Propranolol Safe and Effective For Infantile Hemangmentioning
confidence: 99%
“…In addition, in a meta-analysis of 16 studies (2629 cases) and 25 studies (795 cases) published in 1965-2012, 69% of the patients responded to 12-month corticosteroid therapy, but the response rate to propranolol was 97% with a significant difference. 191 In periorbital hemangiomas, the response rate to propranolol was found to be significantly higher than that to corticosteroid by meta-analysis of papers published before 2013, 192 and propranolol showed the strongest effect against airway e150…”
Section: E149mentioning
confidence: 99%